Oro, plata, mata - Reyes, Jose Javier; Navarro, Jesus; Concio, Charo Santos; Gallaga, Peque; Gil, Cherie; Andolong, Sandy; Lorena, Liza.; Torre, Joel.; Asensio, Fides Cuyugan; Ojeda, Manny; Valdes, Maya.; Villanueva, Lorli; et al. (Quezon City Star Home Video, 1982)
The two aristocratic families in Negros, the Ojedas and the Lorenzons, tried to neglect the realities of war. As the Japanese advance their territories, the families moved to their forest lodge where they met and help some guerillas. Their servant, who joined a group of bandits, looted their house, raped, kidnapped and killed some family members. The war ended and the survivors attempted to reclaim their previous lifestyle but they can never forget what they have lost.
Subtitle: English.
Cherie Gil, Sandy Andolong, Liza Lorena, Fides Cuyugan-Asensio, Manny Ojeda, Maya Valdes, Lorli Villanueva, Ronnie Lazaro, Kuh Ledesma, Joel Torre.
DVD.
Keywords: Upper class families -- Philippines -- Drama; World war, 1939-1945 -- Philippines -- Drama; Motion pictures -- Philippines